Thrombotic Thrombocytopenic Purpura in Pediatric Patients - Niki Shrestha; Ebruphiyo Okpako; Robert W. Maitta (Biomedicines)
Thrombotic thrombocytopenia purpura is a serious disease that can involve complex symptomatology, prolonged hospitalization, and a high risk of mortality if treatment is delayed. This disease is rare, but it is even rarer among pediatric patients. Even though it was first described 100 years ago, the earliest documented case was a pediatric patient. The last three decades have seen the discovery of the pathological mechanisms responsible for its clinical presentation. Symptoms/signs characteristic of microangiopathic hemolytic anemia with significant thrombocytopenia characterize the vast majority of patients. Its pathology centers on the accumulation of ultra-large von Willebrand factor multimers due to an enzyme deficiency that prevents their breakdown. Currently, in pediatric patients, two forms of the disease are known: congenital due to a mutation in the enzyme’s gene and immune-mediated due to enzyme depletion or neutralization secondary to autoantibody formation. With the advent of therapeutic plasma exchanges, immunosuppression, and, more recently, a TTP-specific nanobody, there is reason for optimism that the disease does not necessarily equate to a bad outcome. Thus, the aim of this review is to contrast the congenital and immune-mediated forms of the disease in pediatric patients while presenting them in the context of their pathologic mechanisms, diagnosis, and treatment.